1996
DOI: 10.1016/s0006-3495(96)79204-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shorthorn sculpin antifreeze protein stereospecific binding to (2–1 0) faces of ice

Abstract: In this paper we report the results of our studies on the stereospecific binding of shorthorn sculpin antifreeze protein (AFP) to (2 -1 0) secondary prism faces of ice. Using ice crystal growth and etching techniques together with molecular modeling, molecular dynamics, and energy minimization, we explain the nature of preferential binding of shorthorn sculpin AFP along the [1 2 2] direction on (2- 1 0) planes. In agreement with ice etching studies, the mechanism of preferential binding suggested by molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 18 publications
7
89
0
Order By: Relevance
“…For comparison, vacuum modeling has predicted that SS8 adopts a fully ␣-helical conformation (34), whereas more recent molecular dynamics calculations on SS8 have predicted that the N-terminal cap structure folds the N terminus up and away from the Ala-rich surface of the protein (35). Although direct comparisons between the conformation of residues 1-10 of SS3 and SS8 cannot be made, our results suggest that the first 10 residues of SS3 are aligned approximately parallel to the ␣-helix formed by residues 11-33, with no significant deviation similar to that predicted for SS8 (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, vacuum modeling has predicted that SS8 adopts a fully ␣-helical conformation (34), whereas more recent molecular dynamics calculations on SS8 have predicted that the N-terminal cap structure folds the N terminus up and away from the Ala-rich surface of the protein (35). Although direct comparisons between the conformation of residues 1-10 of SS3 and SS8 cannot be made, our results suggest that the first 10 residues of SS3 are aligned approximately parallel to the ␣-helix formed by residues 11-33, with no significant deviation similar to that predicted for SS8 (35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated using CD spectroscopy that XSS8, the major component, is more helical than XSS3, and it has been proposed that there are two different structural and possibly functional do-mains, the nine-residue N terminus and the alanine-rich helical region between residues 8 and 42 (3). Vacuum phase molecular dynamics studies on SS8, a closely related sequence to XSS8, concluded that the polypeptide conformation resembles an idealized ␣-helix, except for a short section of the N-terminal region (34). This study also proposed that SS8 acts via insertion of the side chains of the Arg and Lys residues into the ice lattice.…”
mentioning
confidence: 99%
“…Jorov et al 34 used Monte Carlo simulation to investigate the effect of hydrophobic interactions between wfAFP and the pyramidal plane on the stability of binding. Similarly, computer simulation has been used to investigate energetically stable binding conformations at ice crystal surfaces for shorthorn sculpin type-I AFP, 35 eelpout type-III AFP, 36,37 sbwAFP 38 and tenebrio molitor AFP. 59 However, in real-world systems, AFPs bind to ice-water interfaces rather than to planes of ice crystals, and AFPs interact strongly not only with ice, but also with water.…”
Section: Computer Simulations Of Afp Binding To Ice Crystalsmentioning
confidence: 99%
“…Thus far, several research groups have used computer simulation for investigating the stable binding conformations of AFP at an ice crystal plane. [30][31][32][33][34][35][36][37] Recently, we also used MD simulation to analyze the molecular-scale growth kinetics at an ice-water interface to which AFP was bound. 38,39 These computer simulation studies have contributed to the understanding of the molecular-scale mechanism of ice growth inhibition by AFPs.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the AFPs, AFGP researchers have been divided over the importance of hydrogen bonding and its role in the mechanism of action. While it has been proposed that the hydrophilic interactions between polar hydroxy groups and the water molecules on the ice surface are extremely important, 170 others have invoked the idea that entropic and enthalpic contributions from hydrophobic residues are crucial in the binding of an AFGP to an ice surface. Despite the fact that significant entropic contributions are likely to be gained upon the exclusion of water from the protein and ice surfaces, a definitive mechanism invoking hydrophobic and/or hydrophilic interactions with emphasis on the role they play in adsorption of the antifreeze to the ice surface has failed to emerge.…”
Section: Antifreeze Proteinsmentioning
confidence: 99%